Humanizing and improving the judicial decision making in Malaysia : exploring the role of social workers in the courts of Malaysia - Laxman, Lekha (2007)
This paper aims to explore the additional roles professional social workers in Malaysia can play in humanizing and improving the judicial decision making process. It is essential that the courts be given the valuable as well as constructive input of professional social workers at various stages of court’s processes. This study will provide an initial assessment of the areas and the extent to which professional social workers can help Malaysian courts to expedite case processing; accurately track cases; increase the amount of information available to the court; improve communication between the court and social service agency; and improve communication with the families involved in the system.